Enumeration and Characterization of Human Memory T Cells by Enzyme-Linked Immunospot Assays - Sandra A. Calarota; Fausto Baldanti (Clinical and Developmental Immunology)
The enzyme-linked immunospot (ELISPOT) assay has advanced into a useful and widely applicable tool for the evaluation of T-cell responses in both humans and animal models of diseases and/or vaccine candidates. Using synthetic peptides (either individually or as overlapping peptide mixtures) or whole antigens, total lymphocyte or isolated T-cell subset responses can be assessed either after short-term stimulation (standard ELISPOT) or after their expansion during a 10-day culture (cultured ELISPOT). Both assays detect different antigen-specific immune responses allowing the analysis of effector memory T cells and central memory T cells. This paper describes the principle of ELISPOT assays and discusses their application in the evaluation of immune correlates of clinical interest with a focus on the vaccine field.